2007
DOI: 10.1038/sj.bjc.6604066
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy, body mass, and the risk of colorectal cancer among postmenopausal women from Germany

Abstract: Previous studies have reported inconsistent results regarding the modifying effect of hormone replacement therapy (HRT) on the association of body mass index (BMI) and the risk of colorectal cancer (CRC) among postmenopausal women. We assessed the use of HRT and BMI in 208 postmenopausal women with histologically confirmed incident CRC and 246 controls in a population-based case -control study in Germany (DACHS study). Ever use of HRT was strongly associated with reduction of CRC risk (adjusted odds ratio 0.41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 39 publications
3
13
1
2
Order By: Relevance
“…We investigated this hypothesis by testing an interaction between history of colonoscopies and MHT use; the inverse association between estrogens alone and risk of colorectal cancers was restricted to women who had a personal history of colonoscopy, although the interaction term was only borderline statistically significant. However, this interaction could only explain part of our results and was not observed in two previous studies which investigated it [24,47].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…We investigated this hypothesis by testing an interaction between history of colonoscopies and MHT use; the inverse association between estrogens alone and risk of colorectal cancers was restricted to women who had a personal history of colonoscopy, although the interaction term was only borderline statistically significant. However, this interaction could only explain part of our results and was not observed in two previous studies which investigated it [24,47].…”
Section: Discussioncontrasting
confidence: 81%
“…Finally, two recent meta-analyses reported a significantly decreased risk of colorectal cancer associated with both estrogens alone and estrogens combined with progestagens [16,17]. Results concerning the effect of the route of administration of estrogens [13,[18][19][20][21][22] or the site of the tumour [12,13,[23][24][25] are also conflicting.…”
Section: Introductionmentioning
confidence: 97%
“…The identification of ER2 (ER-b) as the predominant subtype present in both colon epithelial cell lines and human colon epithelium samples (Arai et al 2000, Xie et al 2004 as well as its downregulated expression on tumor cells compared with normal have pointed out that ER2 might have a selective and inhibitory effect on the proliferation of colon epithelial cells (Foley et al 2000). Later on, epidemiological and clinical studies have reported that postmenopausal women undergoing hormone replacement therapy (HRT) have a decreased risk of developing CRC (La Vecchia et al 2005, Hoffmeister et al 2007. In support of this anti-proliferative action of estrogens in colonic cells, Foley et al (2000) also reported that ESR2 expression level correlate with CRC patient survival.…”
Section: Introductionmentioning
confidence: 81%
“…Women recruited between January 2003 and October 2004 provided basic information about MHT, including start, end, and duration of use A Rudolph et al: Polymorphisms, HT and colorectal cancer risk www.endocrinology-journals.org (Hoffmeister et al 2007). Between November 2004 and December 2007, detailed information for each period of MHT was collected during the interview.…”
Section: Study Subjectsmentioning
confidence: 99%